BILINGUISMO ESCOLAR OU FAMILIAR? NOVAS EVIDÊNCIAS APONTAM PARA A IMPORTÂNCIA DO CONTEXTO ESCOLAR NO DESENVOLVIMENTO DO CONTROLE INIBITÓRIO - Brentano, Luciana; Fontes, Ana Beatriz (Organon, 2011)
! e positive e" ect of bilingualism on the development of chil-dren’s cognitive functions has been shown across many recent studies inthe # eld. ! e present study had two main objectives: (1) to replicate previ-ous # ndings in the literature by showing bilinguals’ enhanced inhibitioncontrol processes and, (2) to add new evidence to the # eld by demon-strating that school-based bilingualism can also enhance the process ofinhibition control. To test these hypotheses, 59 students, ages 9 and 12,who were either monolingual, home-based bilinguals or school-based bi-linguals, completed the arrow version of the Simon task, which assesseschildren’s ability to deal with con$ icting information, and thus, taps ontoinhibition control processes. Results supported both hypotheses, such thatschool-based bilinguals performed better than monolinguals. Interest-ingly, school-based bilingual children also performed better than home-based bilinguals on the Simon task. ! ese new # ndings are discussed interms of the importance of a strong context for the onset of a bilingualadvantage in cognitive functioning.